Estimating The Cost Of Healthcare Services Delivered To Cutaneous Leishmaniasis Patients In Qom Province - Abedin Saghafipour; Ahmad Rahbar; Hadi Hamidi Parsa; Sayed Mohammad Hoseini (Tehran University of Medical Sciences, 2013)
Background and Aim: Cutaneous leishmaniasis (CL) is prevalent in most tropical and subtropical countries of the world and leads to adverse economic consequences. This study was performed to estimate the cost of healthcare services delivered to CL patients in Qom Province. Materials and Methods: Based on the data from 638 CL patients, this cross-sectional study was performed in Qom during 2009-2011. First, using researcher-made forms and based on the accounting documents, the direct and overhead costs of health services in the studied areas were calculated. Then, the out-of-pocket costs per patient were obtained. Finally, the gathered data were calculated using the excel software. Results: In total, more than 1,600 million rials was spent on providing health services to 638 patients with cutaneous leishmaniasis in endemic foci of Qom. The direct healthcare cost was estimated to be about a thousand million and the overhead cost about 600 million rials. Besides, the state cost per patient was estimated to be over 2,520 thousand and the out-of-pocket cost per patient about 240 thousand rials. Moreover, the average total cost per patient was calculated to be 2,760,772 in the studied period. Conclusion : Based on results, considerable costs are spent for CL diagnosis and treatment in Qom. Therefore, health planners should give priority to the prevention of this disease in their programs.